Sex tourism: perception on Malaysia / Norshailla Erna Zainal - Zainal, Norshailla Erna (2013)
Sex tourism is not a new issue in the world of tourism. Some country accept it as a bad image contributor but some taking the advantage and promoting it as a part of economic booster. Corpus of literature mostly showing it is most likely associated with exploitation of children in sex. Unlike other type of tourism, this activity has been perceived as a bad image to the certain countries. Malaysia therefore without doubt is no exception has this kind of activities. However the extent of this activity takes place is still vague. Using qualitative approach employing semi-structured interview, three groups (authorities, travel agents an international tourists) were interviewed. Findings showed conflict in the system between immigration and tourism department make this activity still running illegally. Also, it is assumed that sex tourism is not on “legal-illegal” aspect but more on promoting culture like what it is called as red light district. However, the perception of these groups still believe that it is better to run this kind of activity underground as it affect the credibility of Malaysia that portrayed an Islamic country. Authorities believed and confirmed the sex tourism occurred even in the rural area but there is no promotion encouraging this kind of activity to happen in Malaysia. Most importantly, tourists do not perceive Malaysia as a sex tourism destination but rather the appreciating the nature of this country.